The Influence of Physical Work Environment, Intrinsic Motivation, and Work Discipline on Employee Performance at PT Xing Hao Technology, South Tangerang: A Qualitative Exploration - Arief Budi Santoso; Koki Febriyan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The manufacturing sector in Indonesia is currently experiencing rapid transformation driven by technological advancement, increased production targets, and growing competitive pressures. Under these circumstances, organizations are required to maintain high employee performance while simultaneously creating supportive working conditions that encourage motivation and discipline. This study aims to explore how the physical work environment, intrinsic motivation, and work discipline influence employee performance at PT Xing Hao Technology, South Tangerang. A qualitative descriptive approach was employed to obtain a comprehensive understanding of employees’ experiences and perceptions regarding workplace conditions and performance outcomes. Data were collected through semi-structured interviews, Focus Group Discussions (FGDs), workplace observations, and organizational document reviews. The study involved twelve purposively selected participants consisting of two managers, three supervisors, five operational employees, and two administrative staff members. Data analysis followed Braun and Clarke's (2021) thematic analysis procedures, including familiarization, coding, theme development, review, definition, and interpretation. The trustworthiness of findings was ensured through credibility, transferability, dependability, and confirmability procedures. The findings indicate that a comfortable and safe physical work environment contributes positively to concentration and work efficiency. Intrinsic motivation encourages employees to demonstrate initiative, responsibility, and commitment toward organizational objectives. Furthermore, work discipline strengthens consistency in attendance, compliance with procedures, and timely completion of tasks. The interaction among these factors was found to significantly support employee performance improvement. The study recommends that manufacturing organizations prioritize workplace facilities, employee empowerment initiatives, and disciplinary systems to sustain organizational productivity and competitiveness